The Efficiency/Community Duality in the Emergence of Planning: Cases in Rural Regional Development. (February 2021) - Hibbard, Michael; Frank, Kathryn
The various approaches to planning manifest the intellectual currents of a society. Dualities such as efficiency/community have been central to shaping contemporary planning. The quest for efficiency, the rational utilization of natural, built, and human capital, along with concern for community, the human needs and rootedness of local populations, has been an ongoing theme. We explore that duality in the context of rural regional development and how it shifted from complementary to either/or in the United States from the turn of the twentieth century through the Great Depression and the onset of World War II.